2013
DOI: 10.4329/wjr.v5.i7.264
|View full text |Cite
|
Sign up to set email alerts
|

Choledochocele with pancreas divisum: A rare co-occurrence diagnosed on magnetic resonance cholangiopancreatography

Abstract: We report a case of a 42-year-old male with symptomatic choledochocele and incidental pancreas divisum diagnosed with magnetic resonance cholangiopancreatography (MRCP). Small choledochocele is rare congenital malformation associated with non-specific symptoms and a delay in diagnosis. The coexistence of choledochocele and pancreas divisum is extremely rare with only two case reports published in literature. In both cases MRCP failed to diagnose any biliary or pancreatic abnormality. This case suggests that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…Prior studies suggested that there is about a 30–38% co-existence between the two conditions[21, 22, 23] but a recent larger study suggested the prevalence is as high as 50%[24]. There have reports scattered in the literature with PD co-existing with anomalous pancreatic-biliary junction (APBJ) and choledochal cysts[25, 26, 27, 28, 29]. However, there have been no large-scale studies to support any specific associations between these congenital anomalies.…”
Section: Associated Pancreatic-biliary Anomaliesmentioning
confidence: 99%
“…Prior studies suggested that there is about a 30–38% co-existence between the two conditions[21, 22, 23] but a recent larger study suggested the prevalence is as high as 50%[24]. There have reports scattered in the literature with PD co-existing with anomalous pancreatic-biliary junction (APBJ) and choledochal cysts[25, 26, 27, 28, 29]. However, there have been no large-scale studies to support any specific associations between these congenital anomalies.…”
Section: Associated Pancreatic-biliary Anomaliesmentioning
confidence: 99%
“…To our knowledge, this is the first report of an ectopic opening of the CBD into the duodenal bulb accompanied by choledochocele and PD (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Choledochocele concomitant with PD is also rare, with only three case reports having been published (25)(26)(27); therefore, our case is extremely rare.…”
Section: Discussionmentioning
confidence: 78%